Development of Islamic Cultural History (SKI) Based on Google Sites in 8th grade of Madrasah Tsanawiyah - Nino Indrianto; Parisca Ainul Maulida (Al-Tarbawi Al-Haditsah: Jurnal Pendidikan Islam, 2024)
This research is motivated by the lack of use of digital-based learning media in the learning of Islamic Cultural History (SKI). SKI learning requires innovation in the form of the development of interesting and interactive Google Sites-based SKI learning media to maximize learning. The purpose of this study is to develop SKI learning media based on Google Sites and determine the effectiveness of the media developed in improving SKI learning outcomes. This research uses the Research and Development (R&D) method and uses the ADDIE development model. The results of this research and development are in the form of SKI learning media based on Google Sites. The validated media design shows that it is very valid so it is worth following up for the trial stage. The media attractiveness trial stage obtained results in the category of quite interesting and the media effectiveness test showed that the effectiveness of the media in the category was high so that it was very effective in improving student learning outcomes. This research contributes to the development of digital-based media, especially in SKI subjects. This research also provides pedagogical implications, namely interest, activeness, and improvement of student learning outcomes. Practically, the results of this study can be a reference for educators to design digital-based learning media according to the needs of students. Keywords: Development, Learning Media, SKI, Google Sites.Keywords: Author Guidelines, Template, Article, Tsaqafah, Islamic Civilization.